Strengthening the Pancasila Student Profile in the Implementation of Freedom to Learn in Elementary Schools - Arifin, Arifin; Mas, Sitti Roskina; Bafadal, Ibrahim; Gaib, Marlin (Jurnal Pedagogi dan Pembelajaran, 2024)
Currently, the nation's next generation still has low critical thinking skills, is less creative, and lacks character. This research aims to describe the character strengthening program for Pancasila student profiles, strategies for implementing strengthening character with global diversity and critical reasoning, as well as the impact of implementing strengthening character with global diversity and critical reasoning. This research is included in the type of qualitative research with a case study design. The subjects in this research were the principal, deputy principal, teachers and students. Data collection techniques are carried out through interviews, observation and documentation. The data analysis method was carried out using theme analysis with components of data condensation, data presentation and drawing conclusions. The results of the research show that the program strengthens the character profile of Pancasila students with global diversity, namely religious activities, exhibitions and getting students to care about the environment. The critical reasoning character strengthening program is the implementation of learning based on diagnostic assessment, training and socialization. The implementation strategy for strengthening global diversity of character is socialization regarding Pancasila students, as well as providing real examples of example and discipline. Strategies for developing critical reasoning skills in collaboration with various parties, providing class management guidance and guidance, providing extracurricular activities, and implementing problem posing learning models. There are various positive impacts in implementing character strengthening with global diversity and critical reasoning. The latest information in this research could have implications for providing programs or strategies to strengthen the profile of Pancasila students.